2014
DOI: 10.1016/j.jssc.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature X-ray diffraction measurements of fluorite-related rare earth antimonates Ln3SbO7 (Ln=Nd, Tb) and their magnetic properties

Abstract: Ternary rare-earth antimonates Ln 3 SbO 7 (Ln = rare earths) were prepared, and their structures were determined by X-ray diffraction measurements. They crystallize in an orthorhombic superstructure of cubic fluorite (space group Cmcm for Ln = La, Pr; Ccmm for Ln = Sm -Dy), in which Ln 3+ ions occupy two different crystallographic sites (the 8-coordinated and 7-coordinated). For Ln = Nd, two phases with the Cmcm and Ccmm space groups coexist at room temperature. When the temperature was increased, the Nd 3 SbO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…ions is two. Similar results have been reported for Tb 3 SbO 7 [33]. It is concluded that non-Kramers doublets of Tb 3?…”
Section: Magnetic Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…ions is two. Similar results have been reported for Tb 3 SbO 7 [33]. It is concluded that non-Kramers doublets of Tb 3?…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…One-third of the Ln ions are coordinated by eight oxygen ions, and the remaining two-third of the Ln ions are seven-coordinated. The results of magnetic susceptibility and specific heat measurements on Ln 3 MO 7 (Ln = Nd, Tb; M = Nb, Sb, Ta) showed ''two-step'' magnetic transitions [31][32][33]. It is discussed that the eight-coordinate Ln(1) and seven-coordinate Ln(2) ions individually order at different temperatures.…”
Section: Introductionmentioning
confidence: 92%
“…The estimated S mag value from specific heat measurements 3Rln2 suggests that the degeneracy of the Tb 3+ ions is two. Similar results have been reported for Tb 3 SbO 7 [37]. Therefore, it is considered that Kramers doublets of Ru 5+ ions and non-Kramers doublets of Tb 3+ ions cause the antiferrromagnetic ordering found for Tb 3 RuO 7 .…”
Section: Magnetic Propertiessupporting
confidence: 87%
“…Er ions were restricted to the B site in the final refinement, since allowing for site-disorder refined to a fully ordered phase. In the case where a small impurity peak was present near 2θ = 29°, an impurity phase of Ln 3 SbO 7 was fit using the reported structure. In the final row, PND/PXRD indicates a joint Rietveld refinement on room-temperature powder neutron diffraction data and lab X-ray diffraction data, PXRD represents a refinement on room-temperature lab X-ray diffraction data, and SPXRD represents refinement on low-temperature (100 K) synchrotron X-ray diffraction data.…”
Section: Resultsmentioning
confidence: 99%